ISTILAH-ISTILAH BAHASA JAWA YANG DIGUNAKAN NELAYAN PESISIR PANTAI KULON PROGO - Dyah Arum Wijayanti; Sudartomo Macaryus (Universitas Sarjanawiyata Tamansiswa, 2016)
The objectives of this research are (1) to describe the term form which is used by the fisherman of Kulon Progo coastal areas, and (2) to describe the used of the term which is used by the fisherman of Kulon Progo coastal areas. The type of this research is qualitative research. The data of this research are the terms used by the fisherman of Kulon Progo coastal areas during the fishing processes. The data sources of this research are collected by the fisherman (sea farmer) of Kulon Progo coastal areas. The research instrument is the list of questions (Interview guidline) addressed for the respondents to get the data. The research method and technique are used to collect the data were metode simak (Observation) and metode cakap (interview). The metode simak (Observation) is followed by tapping and recording (teknik rekam and teknik catat) techniques. While the metode cakap (Interview) is followed by teknik pancing then teknik lanjutan cakap semuka. The method of analysis data in this research are agih method. The data analysis results in this research is presented using the informal method. The results of this research are (1) the term form which is used by the fisherman of Kulon Progo coastal areas are classified as; a) the term basic form are tabur, keletan, ngambat, nglernak, nggardan, angsur, krembak, leter, paweh, penikel, ngletek, rumpon, timbel, blong, kumbol, katir, kandem, and mentas, b) the term affixes form are njala, nyerang, nyiker, nyoping, ngriwik, nggragal, njamur, spining, rolling, and ngetem, c) the terms form of combined words which is categorized as phrases are banyu kebak, banyu rosa, mesin perahu, dudukan mesin, and dek perahu also it can be a form of compound words such as nelung in, tlale gajah, jaring eret, jaring ciker, jaring serang, pancing senggol, and pancing rawe, (2) the terms are used by the fisherman of Kulon Progo coastal areas focused on when the term is used. The use of unique terms is used by the skipper and the crew when they are going to fishing and when they are finishing fishing. The terms penawune and nawu are used to communicate before and after fishing. The term of balikan is used to communicate on the ship while they are going to the sea and the term of dirumati is used to communicate between skipper and the crew when they finished fishing.